Development of Distributed Measurement and Control Systems for Application in Electrical Energy Systems - Gajić, Tomislav M; Sarić, Goran; Janković, Marko (Proceedings, Electrical engineering institute "Nikola Tesla", 2013)
In this paper, the LPC1766 microcontroller-based network-capable application processor (NCAP) system is described. This system is intended to be used in modern distributed control and monitoring systems for application in power plants and industry, as well as in modern electricity distribution networks. For this, it is necessary to analyse different aspects of the system, such as signal processing or communication requirements. The chosen microcontroller has enough resources to satisfy the requirements of a transducer interface module (TIM). Beside the realization of NCAP and TIM controllers it is necessary to develop the necessary measurement modules in order to realize measurement-control systems. The developed layout could be connected by actuators to the local area network (LAN) as well. If the local LAN is connected to the internet, it is possible to monitor and configure measurement modules from the remote site. Having in mind the growing complexity in control systems, it has been a real challenge to detect and diagnose problems in today’s large scale distributed systems. Implementation of the proposed module could potentially reduce the time required to extract necessary information from the abundant quantity of information that is usually provided by complex distributed systems